GIS QUANTUM USAGE (QGIS) TO THE CHARACTERIZATION AND DELIMITATION OF A DEGRADED AREA BY BASALT MINING ACTIVITY IN THE MUNICIPALITY OF TENENTE PORTELA (RS) - Turchetto, Natieli Luisa; Queiroz, Rosemar; Peyrot, Caroline; Patatt, Eduardo Ruwer; Langner, Carlos Henrique; Ochoa, Leonardo; Koppe, Ezequiel (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The rise construction developed an accelerated process of extracting rock , increasing the number and extent of the quarries are in Brazil . This activity of extracting rock causes several changes in the environment , monitoring of these degraded areas through the use of environmental zoning is required. To monitor the extraction of basalt from the municipality of Tenente Portela ( RS ) mine , we used to use Quantum GIS ( QGIS ) software to characterize the area , effecting the delimitation of the area of mining digging and regions deposit tailings , access roads and points of interest in the area in question . For each contour were nominated for best viewing points on the boundaries . The Quantum GIS software is shown , using the tools offered by them for handling spatial data , a good geotechnical method to aid in planning the recovery of degraded area because the software offer data collection mechanisms that facilitate the study of the state of area in question .